Enterprise social media at work: web-based solutions for employee engagement. Issue 7 (10th October 2016) - Sharma, Anshu; Bhatnagar, Jyotsna
Abstract : Purpose: The paper aims to highlight the role of enterprise social media as an internal workplace tool for employee engagement purposes. Design/methodology/approach: The paper provides a viewpoint on how social media can be used internally by organizations after considering both academic and practitioner literature in the respective field. Findings: The paper posits that organizations should move beyond using social networking tools for recruitment and branding purposes and take a step further to use social media tools internally for employee engagement initiatives. It provides practical implications for managers to embrace social media as an engagement tool and to increase employees' participation on such media. Research limitations/implications: The paper provides implications for both researchers and practitioners for using social media as a strategic employee engagement initiative and devising appropriate social media and human resource strategies to do so. Originality/value: The paper offers insights into how enterprise social media can be used as an internal communication tool for engaging employees in this technologically connected era.